2009
DOI: 10.1111/j.1742-4658.2009.07004.x
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of mitochondrial DNA damage and bioenergetic dysfunction in CSB defective cells

Abstract: Cockayne syndrome (CS) is a severe, complex, progressive and autosomal recessive disease characterized by developmental, skeletal, neurological and muscular failure, as well as a premature aging phenotype [1]. Patients with CS can be assigned to two different complementation groups, with the majority carrying mutations in the CSB gene [2]. A clinically identified CSB truncation (CS1AN) has been genetically introduced into a mouse, which displays similar but milder CS phenotypes [3]. The CSB protein plays disti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 38 publications
2
46
0
1
Order By: Relevance
“…Oxidative stress has been observed in several neurodegenerative diseases (Trushina and McMurray, 2007), providing a link between our findings of increased ROS production and decreased autophagy to the neuropathology seen in CS. These findings could also explain the accumulation of lesions found in mitochondria from CSB deficient cells (Muftuoglu et al, 2009;Osenbroch et al, 2009;Aamann et al, 2010;Kamenisch et al, 2010). The in creased oxygen and glucose consumption we observe indicates a state of cellular energy deprivation.…”
Section: Mrimentioning
confidence: 48%
“…Oxidative stress has been observed in several neurodegenerative diseases (Trushina and McMurray, 2007), providing a link between our findings of increased ROS production and decreased autophagy to the neuropathology seen in CS. These findings could also explain the accumulation of lesions found in mitochondria from CSB deficient cells (Muftuoglu et al, 2009;Osenbroch et al, 2009;Aamann et al, 2010;Kamenisch et al, 2010). The in creased oxygen and glucose consumption we observe indicates a state of cellular energy deprivation.…”
Section: Mrimentioning
confidence: 48%
“…Results of Kamenisch and colleagues indicated that the proteins directly interact with mtDNA and OGG1 (43), where they stabilize repair complexes at the mitochondrial membrane (1). In addition, mtDNA damage has been shown to accumulate in CSB-defective cells (61).…”
Section: Transcription-coupled Repair: Csa Csb and Xpgmentioning
confidence: 99%
“…Our data suggest that under normal intracellular ATP concentrations, hEndoV is inactive. Previous studies have demonstrated that in response to cellular insults such as methylnitronitrosoguanidine, arsenite, hydrogen peroxide, or menadione, intracellular ATP levels drop significantly, probably due to activation of poly(ADPribose) polymerase, which depletes energy stores in the cells (35)(36)(37). Dependent on dose and exposure time, ATP stores may be reduced with 70 -80%, which gives an ATP concentration that alleviates hEndoV inhibition in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Among the other metabolites in the cells, ATP is abundant reaching millimolar concentrations in most cell types (33). Furthermore, the intracellular ATP concentration is known to fluctuate and for example, under certain stress conditions, like oxidation and arsenite exposure, a large reduction is seen (34,35). Therefore, ATP was included in activity assays for hEndoV and intriguingly, 1 mM ATP almost completely inhibited hEndoV activity (Fig.…”
Section: Regulation and Relocalization Of Hendovmentioning
confidence: 99%